The efficiency enhancement of single-layer solution-processed blue phosphorescent organic light emitting diodes by hole injection layer modification - Yeoh, K.H. (Institute of Physics, 2014)
Poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) PEDOT : PSS is extensively used as a hole injection layer (HIL) in solution-processed organic light emitting diodes (OLEDs). The high work function of a HIL is crucial in improving OLED efficiency. The work function of PEDOT : PSS is usually around 5.1–5.3 eV. By adding perfluorinated ionomer (PFI), the work function of PEDOT : PSS has been reported to reach as high as 5.95 eV. We investigated the effects of PFI-modified PEDOT : PSS in a single-layer solution-processed blue phosphorescent OLED (PHOLED). We observed that high concentrations of a PFI in PEDOT : PSS has detrimental effects on the device efficiency due to the low conductivity of the PFI. Using this approach, blue PHOLEDs with efficiencies of 9.4 lm W−1 (18.2 cd A−1) and 7.9 lm W−1 (20.4 cd A−1) at 100 cd m−2 and 1000 cd m−2, respectively, were demonstrated.